Integration and Optimization of Software to Control Robotic Arms: A Comprehensive Study on Modeling, Hardware Implementation, and PID Tuning - Yadav, Sandeep; Kumar, Sunil; Goyal, Manoj (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Software-controlled robots are the most common type of robotic arms, and their integration is critical to the progress of industries. In this study article, a robotic arm is created using SolidWorks and then its hardware implementation is finished following virtual inspection. Using techniques for higher-order system control such as Genetic Algorithm (GA), Ziegler-Nichols (Z-N), Ant Colony Optimisation (ACO), and Particle Swarm Optimisation (PSO), the movement and design of the DC servo motor’s PID controller are accomplished through PID tuning. In particular, the Genetic Algorithm (GA) is used to improve robotic arm control. MATLAB Simulink simulates the software-based control of the robotic arm and offers a graphical user interface with easily navigable settings. This paper describes in detail how the robotic arm was created step by step and how its hardware and software were implemented. Additionally, Arduino hardware is used for data collecting and control system assessment when observing and evaluating the robotic arm’s output features. A range of input variables are tested using the robotic arm.